Model predictive control for current balancing in a four-phase buck converter - A. F. Yahaya, Jabbar; Mansor, Muhamad (Gazi University, 2016)
Multiphase buck topology offers smaller ripple current and lower component ratings. This, however, compromises unbalanced output current between each phase of an inductor which leads to over-current and inductor saturation issues. Often when discussing the linear control schemes, it involves the use of superposition theorem to understand the system’s response. However, the limitation of superposition theorem in this application is that it assumes the circuit to be completely linear. For components with nonlinear behaviour such as power switches and diodes, the analytical results may not be accurate resulting to unexpected behaviour as the algorithm is implemented on a real system. Hence, the use of a more advanced control scheme is necessary to improve a system with a non-linear characteristic. This paper proposes a current limit control (CLC) consists of MPC for inner loop control and PID for outer loop control for phase current balancing in a four-phase buck converter. The controller is designed to achieve balanced current for each phase with acceptable response time. The proposed system is designed using MATLAB/Simulink simulation software and verified by a laboratory prototype with a TMS320F28335 as the main controller. Simulation and experimental results are provided to validate the system performance.